Infection control and management strategies in Acupuncture and Physiotherapy Department of the Traditional Chinese Medicine institution (中医医疗机构针灸理疗科感染控制与管理策略) - WANG Yuena (王岳娜); REN Guqun (任顾群); TANG Min (唐敏) (中西医结合护理)
Given the widely use of acupuncture in clinical settings, more efforts should be paid on the infection control and management strategies in Acupuncture and Physiotherapy Department of the Traditional Chinese Medicine institution. This paper analyzed the potential risks of nosocomial infection, infection control and management strategies, and provided reference for the standardization of infection control in relevant departments. (针灸疗法在临床应用广泛, 针灸理疗科是医院感染管理的重点科室。本文从针灸理疗科的感染隐患、控制与管理策略等方面进行总结, 以期为进一步规范相关科室的感染防控提供可靠参考。)